Self Management and Immune Status Diabetes Mellitus Patients (STIKES Telogorejo Semarang, 2022)
Diabetes mellitus (DM) self management can improve health problems due to diabetes mellitus. DM Patients are susceptible to various infections due to decreased immunity. Research on the effect of self management on the immune status of patients with diabetes mellitus is still limited. Increased blood glucose for a long time and not getting good management can have an impact on all body systems, including the immune system which triggers the emergence of infectious diseases and the public perception of DM patients getting sick easily becomes something that is considered true. This study aimed to investigated the relationship between self management and the immune status of diabetes mellitus patients. We use questionnaires concerning self management and seeing the results of laboratory examinations for leukocyte types. This study involved the participation of 40 patients. The median score of self management was 2,5 days in 7 days prior to treatment. the lowest self-management behavior was physical exercise and foot care with a median was 1.3 and 1.25 days, and the highest was diet regulation behavior as much as 2.8 day. The median of leukocytes, lymphocytes and monocytes were 12.4, 25.2, and 4.2 mg/dl. There was no correlation between self management and the immune status of DM. Although there is no relationship between self management and immune status but all patients have self management behavior below 50%. Self management also needs to be improved so that the immune status is better.